Running Economy (Articles Review) - Akalu (PhD scholar), Demeku (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2022)
Running economy (RE) is typically defined as the energy demand for a given velocity of submaximal running, and is determined by measuring the steady- state consumption of oxygen (VO2) and the respiratory exchange ratio. Running economy (RE), particularly for distance runners, is regarded as a crucial physiological indicator for endurance athletes. In this review, the definition and measurement of RE are examined, as well as the physiological and biomechanical variables that affect or determine RE. Maximum oxygen uptake (VO 2max), the capacity to maintain a high percentage of VO 2max for a sustained length of time, and running economy all contribute to running performance. Comparatively less research has been done on running economy than on the other parameters. The typical method is to assess running economy as steady state oxygen uptake (VO 2) at intensities below the ventilator threshold. The traditional technique of evaluation is an extrapolation to a typical running speed (268 m/min) or as the VO 2 needed to run a kilometer. Though a smaller frame size and a thinner lower leg may be the main contributing variables, people of East African descent may generally be more economically successful. Though high-intensity running may be a prevalent factor working to enhance the economy, strategies for doing so have yet to be developed. Of the numerous metabolic, cardiopulmonary, biomechanical, and neuromuscular characteristics contributing to RE, many of these are able to adapt through training or other interventions resulting in improved RE.